Ipsilateral radial and ulnar artery cannulation during the same coronary catheterization procedure - Koutouzis, M (Hippokratia, 2016)
Background: Switching to femoral after a failed radial approach carries an increased risk of bleeding complications since the femoral artery puncture is performed in patients already anticoagulated. Moreover, dedicated radial operators find it more and more difficult to use the femoral approach, and ulnar artery cannulation provides them with the opportunity to further reduce its use. Our objective was to evaluate the feasibility and safety of ipsilateral radial and ulnar artery cannulation during the same coronary catheterization procedure. Methods: We performed a retrospective analysis of all cardiac catheterizations, from January 2015 until June 2016, with initial radial approach and conversion to ipsilateral ulnar approach. Patients with sheath insertion both in radial and ipsilateral ulnar arteries were further evaluated. Results: Four thousand one hundred and two procedures were performed during the study period, and 3,876 (94.5 %) of them were performed initially through a radial approach. Radial and ipsilateral ulnar catheterization was accomplished in nine patients, resulting in successful catheterization and procedure completion, without any serious complications recorded. Conclusions: Ipsilateral radial and ulnar artery catheterization proved to be feasible and safe, without any serious complications. Hippokratia 2016, 20(3): 249-251